Peningkatan Literasi Sains Siswa Sekolah Dasar melalui Program FIRE UP - Yuana, Haris; Lukma, Hazairin Nikmatul; Sofiyana, Marinda Sari (Penerbit Widina, Widina Media Utama, 2025)
The FIRE UP program was implemented as an initiative to enhance science literacy and to empower elementary school students. The program activities began with the administration of a pretest, followed by interactive outreach sessions, continued with simple training on the development of solar panel–based products, and concluded with the administration of a posttest. The pretest–posttest results indicated a significant increase in students’ knowledge, motivation, and skills in the field of science and technology, as evidenced by a rise in the average score of 21.43%. Overall, the FIRE UP program was found to be effective and feasible to be implemented periodically to improve science literacy among elementary school students.ABSTRAKProgram FIRE UP dilaksanakan sebagai salah satu upaya untuk meningkatkan literasi sains serta pemberdayaan siswa sekolah dasar. Kegiatan dilaksanakan dimulai dari pelaksanaan pretest, sosialisasi interaktif, dilanjutkan dengan praktik sederhana mengenai pembuatan produk berbasis panel surya, kemudian pelaksanaan posttest. Hasil pretest-posttest menunjukkan adanya peningkatan signifikan pada pengetahuan, motivasi, dan keterampilan siswa dalam bidang sains dan teknologi, yang didukung oleh kenaikan nilai rata-rata sebesar 21,43%. Secara keseluruhan, FIRE UP dinilai efektif dan layak diimplementasikan secara berkala untuk meningkatkan literasi sains bagi siswa sekolah dasar.